2012
DOI: 10.1021/bi3007302
|View full text |Cite
|
Sign up to set email alerts
|

Role of Met80 and Tyr67 in the Low-pH Conformational Equilibria of Cytochrome c

Abstract: The low-pH conformational equilibria of ferric yeast iso-1 cytochrome c (ycc) and its M80A, M80A/Y67H, and M80A/Y67A variants were studied from pH 7 to 2 at low ionic strength through electronic absorption, magnetic circular dichroism, and resonance Raman spectroscopies. For wild-type ycc, the protein structure, axial heme ligands, and spin state of the iron atom convert from the native folded His/Met low-spin (LS) form to a molten globule His/H(2)O high-spin (HS) form and a totally unfolded bis-aquo HS state,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
63
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(71 citation statements)
references
References 103 publications
8
63
0
Order By: Relevance
“…This is diagnostic of a molten globule organization of the hemo-protein that is characteristic of many non-native cytochrome c states induced by guanidine hydrochloride, low pH, and elevated temperature, or formed when cytochrome c binds to anionic phospholipid vesicles, micelles, polyanions, and electrodes. This high spin heme iron was also found in microperoxidases produced by tryptic digestion of cytochrome c resulting in the loss of the sixth coordination bond and markedly elevated peroxidase activity (34,35). Therefore we used electronic absorption spectroscopy to spectrally distinguish between the high spin and low spin ferric hemes (36 -39).…”
Section: Interaction Sites Of ␣-Tos/␣-top On Cytochrome C-tomentioning
confidence: 99%
“…This is diagnostic of a molten globule organization of the hemo-protein that is characteristic of many non-native cytochrome c states induced by guanidine hydrochloride, low pH, and elevated temperature, or formed when cytochrome c binds to anionic phospholipid vesicles, micelles, polyanions, and electrodes. This high spin heme iron was also found in microperoxidases produced by tryptic digestion of cytochrome c resulting in the loss of the sixth coordination bond and markedly elevated peroxidase activity (34,35). Therefore we used electronic absorption spectroscopy to spectrally distinguish between the high spin and low spin ferric hemes (36 -39).…”
Section: Interaction Sites Of ␣-Tos/␣-top On Cytochrome C-tomentioning
confidence: 99%
“…Since coordination of His26 or His33 would require a change in the tertiary structure, it is very likely that His67, which replaces Tyr67 in the distal cavity, binds the iron atom. It is noted that the spectra of the M80A, M80A/Y67A, and M80A/Y67H mutants of yeast iso-1 cyt c at pH 7.2 revealed the presence of only a -OH-Fe-His18 species [26]. However, the low frequency spectrum of the human YHMA mutant (Fig.…”
Section: Y67h-m80a (Yhma)mentioning
confidence: 89%
“…At high ionic strength the statistical coil state I converts to a molten globule, which was later termed A-state [109,110,125]. More recently, Battistuzzi et al used visible absorption and magnetic circular dichroism spectra to probe conformational transition of yeast iso-1 ferricytochrome c and three mutants (M80A, M80A/Y67H, and M80A/Y67A) in the acidic region and a low ion concentration [126]. They found that state III of the wild type first converts into a hexacoordinated high spin state, most likely with water as sixth ligand.…”
Section: Folding and Unfolding Ofmentioning
confidence: 99%